Pengaruh Sulfat Terhadap Kuat Tekan Beton dengan Variasi Bubuk Kaca Substitusi Sebagian Pasir dengan w/c 0,60 dan 0,65 - Fanisa Eki Gradiana Putri; Gunawan Tanzil (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2013)
In order to minimize the damage of concrete structures due to external influences , especially due to sulfate attack that occured naturally in soil and groundwater where the structure is located, and to utilize glass wastes in big cities, a proportion of sand was replaced by glass powder. Two different mix design is calculated based on ACI method (w/c 0.60 and 0.65 ) , with 0%,5%, 10%, 15% and 20% passed a #8 sieve glass powder replacements investigated. Concrete soaked for 7 , 21 and 28 days with 2 types of water were plain water and a 5% sulfate solution . The test results showed that compared to normal concrete for both mix designs, the slump of 20% glass sand replacement concrete was the smallest than the other. Compressive strength of concrete with glass powder substitution is higher than the design compressive strength, and continues to increase with the addition of glass powder content. At 28 days, the compressive strength of specimens with various amount of glass sand replacement were all higher than that of the design strength when soaked in sulfate solution. Keywords : Compressive strength, glass powder, sulfate